The Europeanization of National Policies and Politics of Immigration Between Autonomy and the European Union - Faist, T.; Faist, T.; Ette, A.; Ette, A. (Migration, Minorities and Citizenship, 2007)
The Europeanization of National Policies and Politics of Immigration is the first cutting-edge volume presenting a comparative empirical investigation on the impact of the EU on migration policy at national level. Revealing striking differences, this collection examines traditional member states, new member states as well as non-member states.